Acoustic emission monitoring of hydraulic fracturing using carbon dioxide in a small-scale field experiment. (May 2021) - Ishida, Tsuyoshi; Desaki, Shuich; Kishimoto, Yoshinobu; Naoi, Makoto; Fujii, Hirokazu
Abstract: Carbon capture and storage (CCS) is a promising method for mitigating the greenhouse effect. If we could utilize carbon dioxide (CO2 ) for recovery of geothermal energy and shale gas, CCS will be much more eagerly developed and adopted by compensating its cost. We clarified that hydraulic fracturing (HF) using CO2 tended to induce three-dimensionally sinuous cracks with many secondary branches, which appear to be desirable pathways for energy recovery. However, in a laboratory experiment, it was difficult to evaluate crack extension size and effects of macroscopic pre-existing cracks. Thus, we conducted a HF experiment using CO2 in a hole 10 m long that was drilled in a hot rock mass, thus satisfying the temperature necessary to form supercritical (SC) CO2 . A bi-wing crack 3.33 m in length was induced along the hole; this crack was significantly larger than the approximately 0.5 m long crack we made with water at another site. The fact that acoustic emission (AE) hypocenters distributed in almost perpendicular to an initial HF crack direction without pressure suggested that CO2 could easily intrude and enhance AE occurrence along a pre-existing crack. Focal mechanisms using P wave first-motion polarities elucidated that many compression-dominant AE events were recorded; these were never observed in similar HF experiment we conducted using water. The compression-dominant events were probably induced by crack closure due to the degassing of injected CO2 . Even if CO2 injection induces many AE events, the compressive-dominant events out of them unlikely trigger natural earthquakes because they never create new cracks.